Mucus Hypersecretion and Ciliary Impairment in Conducting Airway Contribute to Alveolar Mucus Plugging in Idiopathic Pulmonary Fibrosis - Peng, Yang; Wang, Zhao-Ni; Xu, Ai-Ru; Fang, Zhang-Fu; Chen, Shi-Ying; Hou, Xiao-Tao; Zhou, Zi-Qing; Lin, Hui-Min; Xie, Jia-Xing; Tang, Xiao Xiao; Wang, De-Yun; Zhong, Nan-Shan (Frontiers in Cell and Developmental Biology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease attributed to complex interplay of genetic and environmental risks. The muco-ciliary clearance (MCC) system plays a critical role in maintaining the conduit for air to and from the alveoli, but it remains poorly understood whether the MCC abnormalities in conducting airway are involved in IPF pathogenesis. In this study, we obtained the surgically resected bronchi and peripheral lung tissues from 31 IPF patients and 39 control subjects, and we sought to explore the morphologic characteristics of MCC in conducting airway by using immunostaining, scanning and transmission electron microscopy. In submucosal regions of bronchi, we found the areas of mucus glands (MUC5B+) were significantly larger in IPF patients as compared with control subjects (P<0.05). In the surface epithelium of three airway regions (bronchi, proximal bronchioles and distal bronchioles), increased MUC5B and MUC5AC expression of secretory cells, decreased number of ciliated cells and increased ciliary length were observed in IPF patients than control subjects (all P<0.05). In addition, the mRNA expression levels of MUC5B were up-regulated in both bronchi and peripheral lung of IPF patients than those of control subjects (P<0.05), accompanied with 93.55% IPF subjects had obvious MUC5B+ mucus plugs in alveolar regions. No MUC5B rs35705950 single nucleotide polymorphism allele was detected in both IPF patients and control subjects. Our study shows that mucus hypersecretion and ciliary impairment in conducting airway are major causes of mucus plugs in alveolar regions and may be closely related to the alveolar injuries in IPF patients.